The poetics of transcendence - Heinämäki, Elisa; Mehtonen, P. M.; Salminen, Antti; Acke, Daniel; Brintnall, Kent L.; Wolosky, Shira; Franke, William; Toikkanen, Jarkko; Mäkelä, Hanna (Amsterdam ; New York : Rodopi, 2015)
The present “turn to religion” has also meant a rekindled interest in transcendence, a concept once deemed a relic of a metaphysical past. This volume approaches transcendence from a particular perspective: that of language and literature seen as a matrix of expression of transcendence and its interplay of immanence. The essays in this volume probe the poetic and literary devices through which transcendence has been solicited, evoked, and generated. This has also meant revisiting the long Christian tradition, not simply to rehabilitate it but as an indispensable source for present writing and thinking. “Thus, ultimately, the present anthology offers no apology for traditional views of transcendence and religious experience but presents original contributions to the poetics of transcendence that are sensitive to religious as well as a-religious languages in literature. It is argued that, in order to rethink meanings and the value of transcendence, rigorous ontological philosophy must once again face up to the imaginative potential of poetics.”--Takakansi
Artikkelien kirjoittajat: Elisa Heinämäki, P. M. Mehtonen, Antti Salminen, Daniel Acke, Kent L. Brintnall, Shira Wolosky, William Franke, Jarkko Toikkanen, Hanna Mäkelä.
Sisältää bibliografisia viitteitä ja hakemistoja.
Julkaistu myös verkkoaineistona.
Keywords: kirjallisuudentutkimus; poetiikka; mystiikka; teologia; transsendenssi; litteraturvetenskap; poetik; mystik; teologi; transcendens; mimeettinen halu